2017
DOI: 10.3390/rs9030220
|View full text |Cite
|
Sign up to set email alerts
|

Calibration and Validation of a Detailed Architectural Canopy Model Reconstruction for the Simulation of Synthetic Hemispherical Images and Airborne LiDAR Data

Abstract: Abstract:Canopy density measures such as the Leaf Area Index (LAI) have become standardized mapping products derived from airborne and terrestrial Light Detection And Ranging (aLiDAR and tLiDAR, respectively) data. A specific application of LiDAR point clouds is their integration into radiative transfer models (RTM) of varying complexity. Using, e.g., ray tracing, this allows flexible simulations of sub-canopy light condition and the simulation of various sensors such as virtual hemispherical images or wavefor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 47 publications
1
12
0
Order By: Relevance
“…A promising alternative to generate realistic hemispherical images from laser scans is to use terrestrial laser scanning (TLS; Bremer et al, ), but TLS provides point‐based samples and is thus not available continuously over larger areas. Moeser et al () further found that ALS‐derived hemispherical images tend to overestimate canopy closure under very dense canopies, probably because small canopy gaps are underrepresented in such conditions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A promising alternative to generate realistic hemispherical images from laser scans is to use terrestrial laser scanning (TLS; Bremer et al, ), but TLS provides point‐based samples and is thus not available continuously over larger areas. Moeser et al () further found that ALS‐derived hemispherical images tend to overestimate canopy closure under very dense canopies, probably because small canopy gaps are underrepresented in such conditions.…”
Section: Discussionmentioning
confidence: 99%
“…A promising solution to overcome these limitations is to approximate light regimes from synthetic hemispherical photographs derived from ALS point clouds and a regional terrain model (Bremer, Wichmann, & Rutzinger, ; Moeser et al, ; Varhola, Frazer, Teti, & Coops, ). We therefore extended a previously developed tool by Moeser et al () to generate such synthetic hemispherical images to include the following new properties: (a) topographic shading and accounting for the accurate position of canopy elements on sloping terrain and (b) distinguishing between diffuse and direct light reaching the forest understorey.…”
Section: Introductionmentioning
confidence: 99%
“…TLS has emerged as among the most promising remote sensing technologies, providing detailed, spatially explicit, 3D information on plant structure, for operational applications in a wide range of disciplines related to the extraction of plant morphological features. These applications include, as reported in previous literature, the estimation of forest biophysical parameters such as gap fraction [68] and leaf area index [25,69]. These methods mostly aim to extract the vertical and horizontal distributions of biophysical variables or to determine an empirical correlation formula between laser scanning and in situ data sets.…”
Section: Discussionmentioning
confidence: 99%
“…Canopy morphology and structure are visualized on computer, and relevant parameter information such as canopy height and volume are extracted by the developed object-based image analysis (OBIA) algorithm. These data can provide theoretical basis and technical support for the intelligent control, monitoring, and management of orchards [5,6].…”
Section: Introductionmentioning
confidence: 99%